An Empirical Investigation of Trade Flows Between Australia and its Major Trading Partners - Samuel Belicka; Ali Salman Saleh (Australasian Accounting, Business and Finance Journal, 2015)
This study introduces Net Export (NX) models to examine the determinants of the trade flows between Australia and eight selected trading partner (TP) countries (China, France, Germany, Malaysia, Singapore, Thailand, United Kingdom, United States of America) in four selected Trade Deficit (TD) categories (Pharmaceutical Products; Nuclear Reactors, Boilers, Machinery and Mechanical Appliances; Electrical Machinery and Equipment; Sound Recorders and Producers, and Vehicles Other Than Railway or Tramway Rolling-Stock). A total of 29 NX models are estimated, which are based on both the monetary and Quantity (QTY) values. Findings in this study suggest that macroeconomic variables such as money supply, interest rates and savings rates have no-significant effect in the determination of the NX levels in the selected categories. This highlights that monetary policy cannot influence the NX levels in the selected TD categories in Australia. This study also identifies some policy implications which arise from this paper.
Keywords: Australia; Trade deficit; Trading partners; Net export models; Estimation